2023
DOI: 10.1177/10815589231151232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinicopathological characteristics and response to neoadjuvant systemic therapy in patients with HER2-low-positive and HER2-zero breast cancer

Abstract: Previous studies have observed that human epidermal growth factor receptor 2 (HER2)-low-positive patients and HER2-zero patients have different prognoses. This study was conducted to investigate whether there are differences in clinicopathological characteristics and the response to neoadjuvant systemic therapy (NST) defined as systemic treatment prior to surgery between HER2-low-positive patients and HER2-zero patients. We retrospectively analyzed the data of patients with HER2-negative breast cancer who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several other studies have also revealed the higher prevalence of positive HR in HER2-low tumors when compared with HER2-zero and HER2-positive tumors [ 25 27 ]. Zhang et al further reported a significantly lower Ki67 expression level in HER2-low tumors when compared with HER2-zero [ 9 ], with other studies reporting similar conclusions [ 27 , 28 ]. Moreover, HER2-low tumors are more likely to exhibit histological Grade 2 than HER2-zero (59.3% vs. 34.4%, p < 0.001) and HER2-positive (59.3% vs. 39.6%, p < 0.001) tumors.…”
Section: Clinical and Histological Characteristicsmentioning
confidence: 80%
“…Several other studies have also revealed the higher prevalence of positive HR in HER2-low tumors when compared with HER2-zero and HER2-positive tumors [ 25 27 ]. Zhang et al further reported a significantly lower Ki67 expression level in HER2-low tumors when compared with HER2-zero [ 9 ], with other studies reporting similar conclusions [ 27 , 28 ]. Moreover, HER2-low tumors are more likely to exhibit histological Grade 2 than HER2-zero (59.3% vs. 34.4%, p < 0.001) and HER2-positive (59.3% vs. 39.6%, p < 0.001) tumors.…”
Section: Clinical and Histological Characteristicsmentioning
confidence: 80%
“… 7 , 9 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 A higher proportion of HER2-low (55%-91%) versus HER2 IHC 0 (34%-82%) tumors are HR+. 9 , 22 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Additionally, a continuous association exists between higher estrogen receptor expression and higher prevalence of HER2-low expression. 32 …”
Section: Clinicopathologic Features and The Prognostic Role Of Her2-l...mentioning
confidence: 99%
“…Robust differences in other clinicopathologic features have not been identified between HER2-low and HER2 IHC 0 breast cancer. Differences in tumor size, tumor grading, Ki-67 proliferation rate, or nodal status between HER2-low and HER2 IHC 0 breast cancer exist 9 , 22 , 26 , 28 , 29 , 30 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ; however, they are not consistent across studies 9 , 23 , 26 , 27 , 37 , 41 , 45 , 46 , 47 and may depend on HR status. 9 , 22 , 40 , 48 Genomic alteration and prediction analysis of microarray 50 (PAM50) intrinsic subtype differences between HER2-low and HER2 IHC 0 tumors have been observed, 9 , 22 , 48 , 49 but these were largely dependent on HR status.…”
Section: Clinicopathologic Features and The Prognostic Role Of Her2-l...mentioning
confidence: 99%
See 1 more Smart Citation